Access to innovative drugs and the National Reimbursement Drug List in China: Changing dynamics and future trends in pricing and reimbursement - Bérengère Macabeo; Liam Wilson; Jianwei Xuan; Ruichen Guo; Petar Atanasov; Linda Zheng; Clement François; Philippe Laramée (Taylor & Francis Group, 2023)
ABSTRACTBackground and objectives: Multiple reforms aimed at improving the Chinese population's health have been introduced in recent years, including several designed to improve access to innovative drugs. We sought to review current factors affecting access to innovative drugs in China and to anticipate future trends.Methods: Targeted reviews of published literature and statistics on the Chinese healthcare system, medical insurance and reimbursement processes were conducted, as well as interviews with five Chinese experts involved in the reimbursement of innovative drugs.Results: Drug reimbursement in China is becoming increasingly centralized due to the removal of provincial pathways, the establishment of the National Healthcare Security Administration and the implementation of the National Reimbursement Drug List (NRDL), which is now the main route for drug reimbursement in China. There is also an increasing number of other channels via which patients may access innovative treatments, including various types of commercial insurance and special access. Health technology assessment (HTA) and health economic evidence are becoming pivotal elements of the NRDL decision-making process. Alongside the optimization of HTA decision making, innovative risk-sharing agreements are anticipated to be increasingly leveraged in the future to optimize access to highly specialized technologies and encourage innovation while safeguarding limited healthcare funds.Conclusions: Drug public reimbursement in China continues to align more closely with approaches widely used in Europe in terms of HTA, health economics and pricing. Centralization of decision-making processes for public reimbursement of innovative drugs allows consistency in assessment and access, which optimizes the improvement of the Chinese population's health.